A review of the mechanisms and biomarkers of allergen immunotherapy - Wilk, Mateusz; Ptak, Jakub; Tomczyk, Bartosz; Kruczkowska, Adrianna; Kanturski, Andrzej; Gomułka, Krzysztof (Medical Studies/Studia Medyczne, 2021)
Allergen immunotherapy has been shown to be successful in numerous clinical trials, even leading to complete relief of allergic symptoms. However, the molecular mechanisms behind these outcomes remain unclear, substantially hindering introduction of more efficient and safer protocols. The current gold standard of assessing the effects of allergen immunotherapy is a challenge test, which might be both unpleasant and dangerous for patients. Better understanding of the molecular background of allergen immunotherapy would allow us to substitute challenge tests with biomarkers. These might also be used to predict a patient’s response to the treatment. Here, we review current knowledge regarding immune responses to allergen immunotherapy and its potential biomarkers.